2007
DOI: 10.1103/physrevb.75.125208
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of (Ga,Mn)N from first principles

Abstract: The structure of Mn clusters in ͑Ga,Mn͒N and the interactions of the magnetic Mn ions and clusters are studied using first-principles calculations. Curie temperatures are calculated using mean-field and Monte Carlo methods. It is found that joining substitutional Mn ions to clusters is energetically favorable and especially the structures of two to four Mn ions formed around a single N ion are most stable. These clusters are always found to have a ferromagnetic ground state, and ferromagnetic intercluster inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 45 publications
0
25
1
Order By: Relevance
“…The structure of Mn clusters in (Ga,Mn)N and the interactions of the magnetic Mn ions and clusters have been studied through first-principles calculations and T C was evaluated using mean-field and Monte Carlo methods (Hynninen et al, 2007). It was found that joining substitutional Mn ions to clusters is energetically favorable and especially the structures of two to four Mn ions formed around a single N ion are most stable.…”
Section: A Ab Initio Materials Designmentioning
confidence: 99%
“…The structure of Mn clusters in (Ga,Mn)N and the interactions of the magnetic Mn ions and clusters have been studied through first-principles calculations and T C was evaluated using mean-field and Monte Carlo methods (Hynninen et al, 2007). It was found that joining substitutional Mn ions to clusters is energetically favorable and especially the structures of two to four Mn ions formed around a single N ion are most stable.…”
Section: A Ab Initio Materials Designmentioning
confidence: 99%
“…The ideal DMSs should exhibit ferromagnetism at room temperature for practical applications and have a homogeneous distribution of the magnetic dopants. Since Dietl et al theoretically predicted that room temperature (RT) ferromagnetism might exist in wide-band-gap semiconductors [2], the transition metal (TM) doped wide-band-gap semiconductors with room temperature ferromagnetism have been extensively reported, such as TMs-doped AlN [3], TiO 2 [4,5], In 2 O 3 [6][7][8], GaN [9,10] and ZnO [11][12][13][14][15][16]. Whereas no convincing evidence can verify that the observed ferromagnetism in TMs-doped DMSs is intrinsic [17].…”
Section: Introductionmentioning
confidence: 99%
“…GdN may also become useful as a spin injector into GaN, or ferromagnetic Mn-, Fe-, or Gd-doped GaN (see, e.g., Refs. [24][25][26][27][28][29][30][31]). …”
Section: Introductionmentioning
confidence: 99%